2017
DOI: 10.1038/am.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

WO3 mesocrystal-assisted photoelectrochemical activity of BiVO4

Abstract: Self-assembled nanocomposites have gained much attention over the past decade due to their intriguing properties and functionalities. In this work, we developed a self-assembled nanocomposite photoanode composed of an epitaxial BiVO 4 matrix embedded with WO 3 mesocrystals for photoelectrochemical (PEC) applications in the visible-light regime. The orientation of the crystal facet and interface provides a superior template to understand the intimate contact between the two constituent phases. We demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…[26,27] Hence,W O 3 could be an efficient underlayert of orm ah eterojunction with BiVO 4 . [28,29] Such heterojunction band alignment will enhance the transport of electronsf rom the CB of BiVO 4 to that of WO 3 ,w hich in turn will suppress the chances of recombination of photogenerated electronsa nd holes.I ne ffect, the WO 3 underlayer serves as a" hole mirror" to block hole transport to the FTO conductive layer. [30] Forc oating WO 3 on FTO we used magnetron sputtering, which is ac ommercially available process.M etallic Ww as magnetron sputtered on the FTO substrate and then calcined in static air to oxidizet he Wt oW O 3 nanoparticles.B yt his methodauniform coatingo fW O 3 could be obtained on FTO glass ( Figure S7), which serves as the underlayer for the subsequent deposition of the Mo-BiVO 4 film by MOD.F igure 1b displays the typicalc urrent density-versus-potential (J-V)c urvesf or the Mo-BiVO 4 anodes with and without WO 3 underlayer.U pon front illumination using an AM 1.5G solar simulator, the bare Mo-BiVO 4 film of 100 nm thickness showedo nly ac urrent density of around 0.34 mA cm À2 at 1.23 V, which monotonically increased to 1.59 mA cm À2 at 2.0 V. After introducing the WO 3 underlayer onto the MoBiVO 4 film of the samet hickness,asignificant enhancement to photoresponse is evident.…”
Section: Resultsmentioning
confidence: 99%
“…[26,27] Hence,W O 3 could be an efficient underlayert of orm ah eterojunction with BiVO 4 . [28,29] Such heterojunction band alignment will enhance the transport of electronsf rom the CB of BiVO 4 to that of WO 3 ,w hich in turn will suppress the chances of recombination of photogenerated electronsa nd holes.I ne ffect, the WO 3 underlayer serves as a" hole mirror" to block hole transport to the FTO conductive layer. [30] Forc oating WO 3 on FTO we used magnetron sputtering, which is ac ommercially available process.M etallic Ww as magnetron sputtered on the FTO substrate and then calcined in static air to oxidizet he Wt oW O 3 nanoparticles.B yt his methodauniform coatingo fW O 3 could be obtained on FTO glass ( Figure S7), which serves as the underlayer for the subsequent deposition of the Mo-BiVO 4 film by MOD.F igure 1b displays the typicalc urrent density-versus-potential (J-V)c urvesf or the Mo-BiVO 4 anodes with and without WO 3 underlayer.U pon front illumination using an AM 1.5G solar simulator, the bare Mo-BiVO 4 film of 100 nm thickness showedo nly ac urrent density of around 0.34 mA cm À2 at 1.23 V, which monotonically increased to 1.59 mA cm À2 at 2.0 V. After introducing the WO 3 underlayer onto the MoBiVO 4 film of the samet hickness,asignificant enhancement to photoresponse is evident.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies [125][126][127][128], because WO 3 has well-known properties such as its low cost, high chemical stability, and good charge transport activity, BiVO 4 was coupled with this material to overcome the moderate charge transport feature of PEC cells fabricated from pure BiVO 4 to produce PEC cells with robust performance. Nevertheless, these studies at potentials as low as 0.6 V versus RHE still demonstrate charge separation efficiencies of less than 60%.…”
Section: Ferroelectric Oxide Perovskitesmentioning
confidence: 99%
“…In general, the establishment of epitaxial thin film photoelectrode has been widely recognized to maximize the potential of photoelectrode materials in pursuit of a further breakthrough by exploring its fundamental properties. For that reason, recently, various research on the growth of the epitaxial BiVO 4 have been reported, to explore its fundamental properties for PEC water splitting [13,19,[56][57][58][59][60][61][62][63]. Based on many theoretical predictions, the research related to the growth of the epitaxial monoclinic BiVO 4 (a = 5.1956 Å, b = 5.0935 Å, c = 11.6972 Å, β = 90.387 • ) films have been focused on growth along the c-axis.…”
Section: Application Of Facet Engineering In Pec Water Splittingmentioning
confidence: 99%
“…In addition to epitaxial monolayer thin films, many studies have been reported on epitaxial heterojunction thin films. Our group recently reported that the self-assembled BiVO 4 -WO 3 heterostructured thin films could be grown epitaxially in the c-axis orientation to investigate the charge interaction between the BiVO 4 and the WO 3 [59]. The growth of epitaxial BiVO 4 (001) thin films also could be achieved on the SrTiO 3 (001) (STO, a = 3.905 Å) substrate by the insertion of the WO 3 as template layer, which could reduce the lattice mismatch between the BiVO 4 and the STO [13].…”
Section: Application Of Facet Engineering In Pec Water Splittingmentioning
confidence: 99%